Challenges in Diagnosis and Treatment of Male Hypogonadism - Dyah Purnamasari (Interna Publishing, 2024)
Hypogonadism is a condition characterized by diminished or absent production of sex hormones by the testicles in men and the ovaries in women. Hypogonadism is classified into primary and secondary hypogonadism. Each type of hypogonadism can be caused by congenital and acquired factors. There are many factors that contribute to the occurrence of hypogonadism, including genetic and developmental disorders, infection, kidney disease, liver disease, autoimmune disorders, chemotherapy, radiation, surgery, and trauma. This represents the considerable challenge in diagnosing hypogonadism. The goals of treatment include restore sexual functionality and well-being, initiating and sustaining virilization, osteoporosis prevention, normalize growth hormone levels in elderly men if possible, and restoring fertility in instances of hypogonadotropic hypogonadism. The main approach to treating hypogonadism is hormone replacement therapy. Male with prostate cancer, breast cancer, and untreated prolactinoma are contraindicated for hormone replacement therapy. When selecting a type of testosterone therapy for male with hypogonadism, several factors need to be considered, such as the diversity of treatment response and the  type of testosterone formulation. The duration of therapy depends on individual response, therapeutic goals, signs and symptoms, and hormonal levels. The response to testosterone therapy is evaluated based on symptoms and signs as well as improvements in hormone profiles in the blood. Endocrine Society Clinical Practice Guideline recommend therapeutic goals based on the alleviation of symptoms and signs, as well as reaching testosterone levels between 400 - 700 ng/dL (one week after administering testosterone enanthate or cypionate) and maintaining baseline hematocrit. Hormone therapy is the primary modality in the management of hypogonadism. The variety of signs and symptoms makes early diagnosis of this condition challenging. Moreover, administering hypogonadism therapy involves numerous considerations influenced by various patient factors and the potential for adverse effects. This poses a challenge for physicians to provide targeted hypogonadism therapy with minimal complications.